ANALYSIS OF THE EFFECT OF CAPITAL EXPENDITURE, BUSINESS RISK, AND PROFITABILITY ON THE CAPITAL STRUCTURE OF COMPANIES ON PROPERTY INDUSTRY - Tanggor Sihombing; Steven Arfin Susanto (Universitas Multimedia Nusantara, 2021)
Abstract – The objective of this research is to test whether capital expenditure, business risks, and profitability will affect a company's capital structure. The company under study runs in the real estate and property industry which listed on Indonesia Stock Exchange in 2013-2019. The purposive sampling method is used in this research. The sampling data involved 30 companies for 7 years consecutively starting from 2013-2019. In this research, there is one dependent variable, i.e., capital structure, while there are three independent variables, i.e., capital expenditure, business risks, and profitability. This research used multiple linear regression data. Besides that, the data samples are already tested by using the classic assumption method, starting from the normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. Based on the research, the capital expenditure and business risks are not affecting the company capital structure in the real estate and property industry. However, profitability has a significant negative impact on the company's capital structure. Keywords: Business Risk; Capital Expenditure; Capital Structure; Profitability